2006
DOI: 10.1007/s11258-005-9029-8
|View full text |Cite
|
Sign up to set email alerts
|

Moss Responses to Elevated CO2 and Variation in Hydrology in a Temperate Lowland Peatland

Abstract: We studied the effects of elevated CO 2 (180 -200 ppmv above ambient) on growth and chemistry of three moss species (Sphagnum palustre, S. recurvum and Polytrichum commune) in a lowland peatland in the Netherlands. Thereto, we conducted both a greenhouse experiment with both Sphagnum species and a field experiment with all three species using MiniFACE (Free Air CO 2 Enrichment) technology during 3 years. The greenhouse experiment showed that Sphagnum growth was stimulated by elevated CO 2 in the short term, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 50 publications
2
34
0
Order By: Relevance
“…Shading has been found to significantly reduce the C:N ratio of Sphagnum capitula from ~54 to ~27 from peat mesocosms removed from a raised bog in Upper Teesdale, UK (Bonnett, Ostle, & Freeman, ). Although C:N over 100 has been reported for Sphagnum litter (Asada, Warner, & Aravena, ), several studies report values similar to this study of 30–50 (e.g., Limpens, Berendse, & Klees, ; Péli, Nagy, & Cserhalmi, ; Toet et al, ). We also observed that C:N ratio of Sphagnum was similar to the leaves of R. groenlandicum , a result consistent with reported C:N ratios from a range of plant functional types in a shrubby ombrotrophic bog in eastern Canada (Wang & Moore, ).…”
Section: Discussionsupporting
confidence: 77%
“…Shading has been found to significantly reduce the C:N ratio of Sphagnum capitula from ~54 to ~27 from peat mesocosms removed from a raised bog in Upper Teesdale, UK (Bonnett, Ostle, & Freeman, ). Although C:N over 100 has been reported for Sphagnum litter (Asada, Warner, & Aravena, ), several studies report values similar to this study of 30–50 (e.g., Limpens, Berendse, & Klees, ; Péli, Nagy, & Cserhalmi, ; Toet et al, ). We also observed that C:N ratio of Sphagnum was similar to the leaves of R. groenlandicum , a result consistent with reported C:N ratios from a range of plant functional types in a shrubby ombrotrophic bog in eastern Canada (Wang & Moore, ).…”
Section: Discussionsupporting
confidence: 77%
“…Mini‐FACE experiments in four predominantly ombrotrophic peat bogs in Finland, Sweden, the Netherlands, and Switzerland showed no effect of elevated CO 2 on Sphagnum biomass over 3 years (Hoosbeek et al, ). In a greenhouse experiment, Sphagnum growth was initially stimulated by elevated CO 2 , but the response did not persist in the second year of exposure, and in the field, Sphagnum responded more to spatial variation in hydrology than to atmospheric CO 2 concentrations (Toet et al, ). In contrast with vascular plants for which effects of elevated CO 2 on photosynthesis and stomatal conductance are well documented (Ainsworth & Long, ), Sphagnum photosynthesis is controlled more by water content (Schipperges & Rydin, ; Williams & Flanagan, ), and stomatal responses are precluded.…”
Section: Discussionmentioning
confidence: 99%
“…Field studies and laboratory experiments show that the CO 2 fertilization effect on plant growth should be smaller in peatlands than in other northern ecosystems. On the one hand, some moss species were found not to be stimulated by elevated CO 2 (Berendse et al, 2001; Toet, 2006). On the other hand, the effects of CO 2 on growth of vascular plants in peatland might be limited by low nitrogen availability in oligotrophic peatlands (Hoosbeek et al, 2001).…”
Section: Discussionmentioning
confidence: 99%